Application of the Pureepatpong and Thummar Equations to Estimate Stature from Ulna Length in Early‑Adult Madurese Individuals - Anung Putri Illahika; Latifah Tazkia Mulyati; Mohammad Syarif (FORIKES, 2026)
Stature is a fundamental anthropometric indicator used in nutritional assessment and pharmacokinetic calculations; however, direct measurement is often challenging in intensive care settings or among individuals with skeletal deformities. Estimation based on ulna length offers a practical alternative. Although numerous formulas have been proposed, none have been specifically developed or tested for the Madurese ethnic group. This study aimed to estimate stature from ulna length among early‑adult Madurese individuals. An analytical observational design with a cross‑sectional approach was employed. A total of 34 students aged 18–29 years from the Faculties of Medicine, Nursing, and Pharmacy at Universitas Muhammadiyah Malang were selected using purposive sampling. Stature was measured using a microtoise, whereas ulna length was assessed using a sliding caliper. Data were analyzed using univariate statistics, independent t‑tests, and linear regression. The findings demonstrated significant differences between actual stature and estimated values generated by existing formulas, with the Pureepatpong equation yielding estimates closest to actual measurements compared with the Thummar formula. Ulna length showed a significant association with stature. In conclusion, ulna‑based measurement is a valid method for estimating stature in early‑adult Madurese individuals. The Pureepatpong formula exhibited superior accuracy and is therefore recommended for application in this population.Keywords: stature estimation; ulna length; early adulthood; Madurese ethnicity; anthropometry